Design of Top Traction Elevator in Building 6 Floor - Sesmaro Max Yuda; Medyawanti Pane; Frengky Elyes (Universitas Sultan Ageng Tirtayasa, 2021)
Various kinds of technology and scientific discoveries produced by mankind have led to innovations in multi-story construction, especially office buildings that are widely built in the city of Jakarta. This research is under construction, in which to find out whether the design used is appropriate and efficient. From the calculation results, the design of an elevator at a capacity of 1000 kg with a speed of 60 Mpm, a car 1600 X 1400 Hoitsway 2430 X 2240 X 2350 obtains a carrying capacity of 1000 kg (13 people) and a power of 6.19 kW which comes from the Harmoni building (6 floors building). While the tensile stress on the elevator rope is 188.8 kg with an allowable tension of 909.1 kg and the age of the rope is 59.69 months or 4.9 years. The pull on the elevator rope is 131.63 kg with an allowable tension of 909.5 kg and the age of the rope is 1115.3 months or 9.6 years. with an elevator carrying capacity of 630 kg (8 people) and a speed of 105 Mpm (1.75 m/s).